Selective laser melting for the preparation of an ultra-high temperature ceramic coating. Issue 2 (1st February 2019) - King, Derek; Middendorf, John; Cissel, Kathleen; Key, Thomas; Carney, Carmen
Abstract: Selective laser melting of a ZrB2, ZrC, and B4 C powder blend was chosen to explore the use of the additive manufacturing technology to prepare dense ceramic coatings on a metallic tungsten substrate. Laser powers between 200 and 400 W were used for the application of the ceramic coatings. Adherent coatings were fabricated; however, a thermal expansion mismatch between the coating and substrate proved to be detrimental to coating integrity after cross-sectioning. Analysis of the microstructure and composition of the resulting coatings was used to elucidate the effects of thermal gradients and the effects of tungsten and SiC impurities on the solidification of the ceramic coatings. To the authors' knowledge, these are the first ultra-high temperature ceramic coatings fabricated with a selective laser melting process.